An Historical Review of Mass Sports Policy Development in China, 1949–2009. Issue 15 (2nd November 2019) - Zhang, Xiaolin; Saunders, John
Abstract: This analysis considers the evolution of China's mass sports policy through four distinct periods between 1949 and 2009. From 1949 to 1957 represented the initial stage which was concurrent with the establishment of 'New China'. In this period, mass sports policies focussed on enhancing fitness for labour and national defence, underpinning a new nationalism. From 1958 to 1976, mass sports policies were viewed as a political tool for social control, contributing to the establishment of the party's absolute leadership and enhancing a sense of esprit de corps and positive teamwork in different departments and areas. From 1977 to 1994, mass sports policy was focussed on the reform of the management system and the construction of a sports culture. From 1995 to 2009, policy moved onwards to equality of opportunity for participation. It is argued that China's mass sports policy has shifted from a unified national perspective to a more human-based standard supported by a variety of policy systems from national to local government. This account shows how mass sports policy has played an active political role in the nation's economic construction and cultural development.